Juridical Review of the Role of Notaries in the Implementation of Anti Money Laundering Programs - Muhammad Yusli Juliansyah; Benny Djaja (PT Publikasiku Academic Solution, 2023)
The Notary profession is always guided by the prevailing laws and regulations including Law Number 30 of 2004 as amended by Law Number 2 of 2014 concerning Notary Positions. This study aims to illustrate the role of Notaries in the implementation of anti-money laundering programs as stipulated in Government Regulation Number 43 of 2015 concerning Reporting Parties in the Prevention and Delivery of Anti-Money Laundering Crimes submitted to the Center for Financial Transaction Reporting and Analysis (PPATK). Based on this description, this study uses the Normative Juridical research method